PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KEKERASAN ANTAR PELAJAR YANG DILAKUKAN SECARA BERKELOMPOK ( Studi Penelitian Di Kepolisian Resort Kota Lhokseumawe) - Nasution, Prayudi; Nasir, Muhammad; Asmara, Romi (Fakultas Hukum Universitas Malikussaleh, 2024)
This research aims to find out and analyze how the law is enforced for criminal acts of violence committed by students in groups at the Lhokseumawe Police Station, what are the obstacles and efforts in enforcing the law against criminal acts of violence committed by students in groups at the Lhokseumawe Police Station. This research uses empirical research methods and an empirical juridical approach. Data was obtained through field research and library research. Data analysis was carried out qualitatively. Based on the results of research on the resolution of violent crimes committed by students or brawls. Lhokseumawe Police uses the principle of restorative justice (RJ) and refers to the Law on Child Protection and does not override the Criminal Code and Criminal Procedure Code. Brawl cases committed by students are resolved using a restorative justice approach because RJ focuses on restoring relationships and healing the impact of the crime, and is more likely to reduce the possibility of re-offending in the future. Criminal acts that can be resolved with RJ include cases such as theft of small items, brawls, public order disturbances and others. Obstacles to criminal acts of violence committed by students in groups at the Lhokseumawe Police are due to child protection and sensitive handling, the right to be heard, lack of evidence and sanctions, intervention from schools and parents, mediation and diversion processes, the rise of social media, lack of information and capabilities and resources of law enforcement officials. The efforts made by the Lhokseumawe Police include outreach in schools regarding the impacts and efforts that need to be made to overcome brawls. The school also provides sanctions, as well as prevention measures taken by families, including taking good care of children and spending time together. It is hoped that the Lhokseumawe Police, need to provide strict sanctions. Next, it is necessary to provide an understanding of education, morals and morals to students. Parents and teachers need guidance regarding student attitudes.